Electronic participation initiatives in Africa: extraction from literature review perspectives / Isyaku Uba Haruna, Maslinda Mohd Nadzir and Hapini Awang - Uba Haruna, Isyaku; Mohd Nadzir, Maslinda Mohd Nadzir; Awang, Hapini (Penerbit UiTM, 2021)
The main objective of this research is to examine the use of Information & Communication Technologies (ICT) and derive the success factors of eParticipation initiatives according to the electronic government (eGovernment) content evaluation. For this purpose, an African study took place using a two-step methodological technique: 'review of the United Nations' eGovernment survey report; and a wide review from the existing literature. The results suggest that the tools and technologies presently applied are mainly general purpose and not exactly designed for eParticipation. In addition, the results indicated that success factors can be categorized into seven groups of factors: government commitment; usability; combination of both online and offline networks; comprehensive communication and encouraging plan; security and privacy, organizational issues; and topics complexity. A comparison with reviewed factors of eParticipation initiatives success suggests there are similarities and significant differences on ICT usage among countries. This study anticipates that its results could be of interest to practitioners as it highlights some knowledge in a practical way. Furthermore, this research could be of interest to researchers as it contributes in validating eParticipation evaluation models.